Adoption levels, barriers, and incentive mechanisms for scaling integrated rice-fish system and alternate wetting and drying in Cote d’Ivoire and Nigeria - Akpoffo, A.M.Y.; Kouadio, K.S.A.; Yeo, Y.S-A.; Dossou-Yovo, Elliott Ronald (Africa Rice Center, 2023)
This study employed a participatory approach to assess the perceived adoption levels, barriers, and incentive mechanisms for the widespread implementation of the alternate wetting and drying irrigation method and integrated rice-fish system. The findings revealed that the current perceived adoption rates for both technologies were low, ranging from 10 to 15%. Across various countries and rice-growing environments, the primary barriers hindering the widespread adoption of alternate wetting and drying included a lack of information, absence of a permanent water source, and environmental unsuitability. Key incentives for widespread adoption of alternate wetting and drying included access to agricultural extension services, availability of quality and suitable seeds, and the promise of higher rice yields. Conversely, the major barriers for the adoption of the integrated rice-fish system included limited access to fish markets, high prices of fish feed, and poor quality of available fish feed. Incentives for adopting the integrated rice-fish system encompassed access to credit and finance, availability of water resources enabling ecosystem suitability, and landownership. The framework utilized in this study presents a valuable tool for governments, development organizations, and the private sector to inform investment decisions when scaling locally relevant Climate-Smart Agriculture (CSA) innovations.